The ‘School of Structural Analysis’ in Modern Russian Sinology - Stanislav Rykov (Journal of World Philosophies, 2016)
The second half of the twentieth century was marked by the appearance of a new and original school in Russian sinology which uses the so-called methodology of ‘structural analysis’ in studying Chinese classics and attempts to find an authentic methodology among Chinese philosophers themselves. Its most influential representatives are V.S. Spirin, A. M. Karapetyants, A. I. Kobzev and A. A. Krushinsky. The main thesis of Russian ‘structuralists’ is that the composition of the ancient Chinese text influences its content directly. A composition of a text is derived from a configuration of its parallel passages. The method of ‘structural analysis’, therefore, aims to detect and describe these parallelisms, and then makes some interpretation of them. The present paper gives a short introduction to the history of this school, its main representatives and concepts, and also shows how the method of ‘structural analysis’ works on some concrete examples.